Death Risk Score Model of Hospitalized COVID-19 Patients: A Cohort Study - Gustavo A. Cruz; Thais B. Boteon; Henrique Pott; Sigrid de Sousa dos Santos; Bruna Dias de Lima Fragelli; Cynthia Aparecida de Castro; Joice Margareth de Almeida Rodolpho; Davi Casale Aragon; Fernanda de F. Anibal; Meliza Goi Roscani (International Journal of Clinical Practice)
Conclusion: The routine laboratory on hospital admission may be a good predictor of mortality during the hospitalization follow-up of COVID-19 patients. A score risk may be adjusted and calculated based on these markers.